Loai Distribution: Properties, Parameters Estimation and Application to Covid-19 Real Data - Loai M. A. Alzoubi; Mohammad M. Gharaibeh; Ahmad M. Alkhazaalh; Mohammed Benrabia (My University, 2022)
In this paper, we propose a new two parameter continuous distribution. It is called Loai distribution. Some statistical properties of this distribution are derived such as: the moment generating function, the moments and related measures, the reliability analysis, and associated functions. Also, the distribution of order statistics and the quantile function are presented. Shannon, Re’nyi and Tsallis entropies are derived. The method of maximum likelihood and some other methods of estimation are used to estimate the distribution parameters. A simulation study is performed to investigate the performance of different methods of estimation. Covid-19 real data applications show that the proposed distribution can provide a better t than several well-known distributions.